Impact of mid Eocene greenhouse warming on America’s southernmost floras - Fernández, Damián Andrés (2021)
A major climate shift took place about 40 Myr ago—the Middle Eocene Climatic Optimum or MECO—triggered by a significant rise of atmospheric CO2 concentrations. The biotic response to this MECO is well documented in the marine realm, but poorly explored in adjacent landmasses. Here, we quantify the response of the floras from America’s southernmost latitudes based on the analysis of terrestrially derived spores and pollen grains from the mid-late Eocene (~46–34 Myr) of southern Patagonia. Robust nonparametric estimators indicate that floras in southern Patagonia were in average ~40% more diverse during the MECO than pre-MECO and post-MECO intervals. The high atmospheric CO2 and increasing temperatures may have favored the combination of neotropical migrants with Gondwanan species, explaining in part the high diversity that we observed during the MECO. Our reconstructed biota reflects a greenhouse world and offers a climatic and ecological deep time scenario of an ice-free sub-Antarctic realm.